Awareness among women towards rape prevention in Taman Indah Permai, Sepanggar, Kota Kinabalu / Celestina Paulus and Lizawati Macin - Paulus, Celestina; Macin, Lizawati (2017)
This chapter focuses on the background of the study, which is on the awareness towards rape prevention among women in Taman Indah Permai, Sepanggar, Sabah. Section 1.0 discusses the background of the study; section 1.2 explains the problem statement and section 1.3 states the research questions. On the other hand, section 1.4 states the research objectives and section 1.5 is on the information regarding the scope of the study. In addition, section 1.6 explains the significance of study and lastly section 1.7 is all about the definition of terms, terminology and concepts.